Ethiopia : Legal and Judicial Sector Assessment - World Bank (Washington, DC, 2013)
The judicial and legal sector of Ethiopia presents a variety of significant challenges. The legal system as it exists today combines elements of both civil and common law1 with traditional practices, resulting in multiple layers intermingling and superimposing distinct types of modern, traditional, and religious laws and processes. This report provides an overview of Ethiopia's current legal system focusing on four key issues: judiciary, access to justice, commercial justice, and sequencing of reform efforts. Other issues are commented upon briefly to provide context and elucidate interconnections between issues. The report focuses mainly on the formal legal system as established by the 1995 Constitution.